Synchronization of Time Period for Settlement of Dispute Payment of Compensation for the Procurement of the Pandaan Malang Toll Road - Mazarini Maulidia Aizza Udin; Abdul Rachmad Budiono; Yenny Eta Widyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Justice in the field of land as a constitutional mandate is a foundation that must be regulated as contained in the provisions of Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia which states,